50 activities for developing people skills - Stewart, Jacqueline 1949- (HRD Press, 2004)
Part of our best-selling 50 Activities series! Comes complete with learning objectives, facilitator guidance, and reproducible materials. Training Objectives: Improve interpersonal skills Enhance management performance.
Print version record
Keywords: Interpersonal relations -- Problems, exercises, etc; Interpersonal communication -- Problems, exercises, etc; Communication interpersonnelle; Problèmes et exercices; Interpersonal communication; Interpersonal relations; Problems and exercises